Preparation and Characterization of Two Component Transparent Zinc Oxide/Silicone Nanocomposites for Power Light Emitting Diodes Encapsulant - Hu, Xiaoyong; Lin, Zhiyuan; Zheng, Youming; Xu, Yuqing (Asian Journal of Chemistry, 2015)
Novel transparent zinc oxide (ZnO)/silicone nanocomposites for power light-emitting diodes packaging with excellent properties including a high transparency, UV-shielding efficiency and thermal properties were successfully synthesized through a three-step reaction routes: (i) ZnO precursor was prepared via homogeneous precipitation method and ZnO nanpoparticles were then obtained by calcination of the precursor at different temperature; (ii) the graft polymerization of surface fractionalized ZnO (m-ZnO) nanoparticles in hydrogen-containing poly(methysiloxane) were investigated and then mixed with terminal-vinyl poly(methylsiloxane) and MQ silixone resin as component B; (iii) the hydrosilylation chemistry of terminal-vinyl polymethysiloxane (as component A) in (ii) with MQ silicone resin and platinum catalysts. The structural properties of the as-prepared ZnO nanoparticles were studied and the nanocomposites were characterized through Fourier transform infrared, themogravimetry and Scanning electron microscope. The optical properties of nanocomposites namely visible light transparency and UV-light shielding efficiency were studied using an ultraviolet-visible spectrophotometer. The results indicated that functionalizations with A151 greatly improved the dispersion of ZnO in silicone due to their high chelating capacities with ZnO and the refractive index of m-ZnO in nanocomposites were changed by chemical grafting. The optical properties of the as-obtained nanocomposites were shown to depend on ZnO particle size and the nanocomposites containing 0.06 % in weight of functionalized ZnO nanoparticels with an average particle size of 96.01 nm after calcination at 400 °C possessed excellent visible-light transparency and high UV-light shielding deficiency. Moreover, the thermal properties of nanocomposites was enhanced with m-ZnO introduced and met the requirements of high-performance electronic packaging for high-power light-emitting diodes encapsulant.